Meningkatkan Minat Baca Peserta Didik Melalui Penggunaan Metode Paikem di Kelas III.A SDN Model Terpadu Madani - Rawina (JKPD (Jurnal Kajian Pendidikan Dasar), 2025)
This research is a type of Class Action Research (CAR) which aims to increase students' interest in reading through the application of the PAIKEM method. The subjects of this research were 32 students of class III.A SDN Model Terpadu Madani consisting of 13 boys and 19 girls. The data collection technique in this research was an observation sheet. The data analysis technique in this research was a quantitative descriptive technique to calculate the percentage value of the observation sheet of student activities and provide an observation sheet. The results of this research are that there is an increase from cycle I to cycle II, namely 56.3% . Thus, it can be concluded that the application of the PAIKEM method can increase students' interest in reading in class III.A SDN Model Terpadu Madani.